(untitled) (Perner’s Contacts, 2014)
The paper is focused on the evaluation of characteristics of passengers, who use the special bus line “Cycle bus” for transportation in urban bus transport (UBT) in Nitra. In the introduction is defined the role and mission of transport as a service and its contribution to inhabitants. Subsequently there is presented a characteristic of the selected bus line within the frame of particular vehicle, its routing and traffic features. The main part of the paper lies in the analysis of realized questionnaire survey among passengers, which synthesis consists in the introduction of model types of passengers travelling by the Cycle bus. Finally, the acquired findings are summarized and areas that may be improved in the future are pointed out.